2020
DOI: 10.1111/josh.12940
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Mental Health Outcomes for Lesbian, Gay, Bisexual, and Heterosexual Youth: A Latent Class Analysis

Abstract: BACKGROUND Lesbian, gay, bisexual, and questioning (LGBQ) adolescents are at increased risk of poor mental health due to minority stress, a chronic stress associated discrimination, social rejection, and victimization brought on by prejudicial attitudes towards LGBQ individuals. To improve understanding of the differential impact of various kinds of victimization on mental health outcomes for LGBQ adolescents, we analyzed data from the 2015 Youth Risk Behavior Survey (YRBS) for victimization and mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There is a need for more social justice approaches to sexual violence prevention that de-silo forms of oppression and that use intersectional, anti-racist frameworks. Hong (2017) suggests several key elements of a social justice approach to sexual violence on college campuses, including understanding intersections of power, identity, and privilege as well as multipronged approaches that collaboratively work across differing campus entities. Other suggestions for centering students with minoritized identities in violence prevention work include integrating anti-oppression frameworks and addressing violence and trauma beyond sexual violence to attend to historical trauma such as systemic oppression (Klein et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for more social justice approaches to sexual violence prevention that de-silo forms of oppression and that use intersectional, anti-racist frameworks. Hong (2017) suggests several key elements of a social justice approach to sexual violence on college campuses, including understanding intersections of power, identity, and privilege as well as multipronged approaches that collaboratively work across differing campus entities. Other suggestions for centering students with minoritized identities in violence prevention work include integrating anti-oppression frameworks and addressing violence and trauma beyond sexual violence to attend to historical trauma such as systemic oppression (Klein et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A 2010 report on climate assessments among 14 institutions of higher education showed that one-third of students with minoritized sexual and gender identities-a group comprised of gay, lesbian, bisexual, and transgender students-experienced harassment (largely coming from other students) and 43% rated their campus climate as homophobic (Rankin et al, 2010) the results of which were later extended to community college students (Garvey et al, 2015), as well as linked to detrimental impacts on academic performance (Garvey et al, 2018). More recent research also found students with minoritized sexual and/or gender identities reported experiencing homophobia and identity-based victimization (Bissonette & Szymanski, 2019), or heterosexism, which has been linked to poor mental health outcomes (Heiden-Rootes et al, 2020). Grouping individuals across gender and sexual identities is commonly done, as in Rankin et al (2010), and, although they may intersect and interact, it is important to remember that these identities are separate and should be disaggregated to better understand campus violence (Linder et al, 2020).…”
Section: Campus Experiences For Students With Minoritized Identitiesmentioning
confidence: 99%
“…This risk has been attributed to LGB adolescents’ higher rates of depression and experiences of bullying and victimization in their schools and communities (De Pedro et al, 2017; Hatzenbuehler, 2011; Kann et al, 2016; Russell et al, 2011). In a recent latent class analysis of data from 15,624 adolescents in the 2015 National Youth Risk Behavior Survey, researchers found that adolescents, regardless of sexual identity, who were categorized as having been bullied or having experienced physical or sexual violence had five times greater odds of reporting severe mental health symptoms (defined as a >60% endorsement probability of five mental health symptoms, including depression, all three aspects of suicidality, and difficulty concentrating) as opposed to reporting low mental health symptoms (defined as <3% endorsement probability of the five symptoms; Heiden-Rootes et al, 2020). Although this study found no marked difference between heterosexual and LGB adolescents in their sample, findings provide evidence that peer victimization greatly increases risk of depression and suicidality and that interventions and policies to reduce peer victimization that takes the form of bullying and physical/sexual violence should be implemented.…”
mentioning
confidence: 99%